(untitled) (Research, Society and Development, 2022)
This article aims to verify the effectiveness of the educational product, the “CAE on the network” application, together with some integrated high school classes (EMI) of a Federal Institute. The application aims to centralize some documents related to student assistance policies (PAE) developed at the institution to facilitate access to this information. This is a quantitative-qualitative study. For data collection, a questionnaire developed for this study was used as an instrument. Data analysis was developed through descriptive statistics, organized into positive and negative aspects. With the study, it was identified that for the students the application "CAE on the network" is organized, they would use it frequently and would indicate its use to colleagues and at reception meetings, which provided greater knowledge about the policies developed in the institution. And they claim that these policies are important for their permanence in the institution. Regarding the effectiveness of the application, students indicate that it facilitates access to student assistance documents, reducing research time. In view of the aspects studied, it is concluded that the application fulfilled its objective of facilitating access to PAE documents, making the research more practical and intuitive, thus being able to be used as an institutional tool in the search for the permanence of students, and in the recognition of these actions as strategies that aim at the democratization of education and the reduction of social inequalities.